STRATEGI KESANTUNAN BERBAHASA ANDY F NOYA DALAM ACARA KICK ANDY DI METRO TV - Ramlah, Ramlah; Charlina, Charlina; Hermandra, Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to describe the strategy of language politeness marker contained in the speech Andy F Noya in Kick Andy event in Metro Tv. The method used in this research is descriptive qualitative method. Data collection techniques in this study is using downloading techniques, refer to and record. Based on the data obtained, language politeness strategies found two hundred fifty-four strategy data and twenty-nine data marker politeness. Based the total amount of data is two hundred and eight three data. Therefore, the most emerging strategy is a strategy that provides question or ask for reasons as much as sixty-three data, from the amount of data found then, Andy F Noya said in Kick Andy show on Metro Tv declared polite. Then the marker found in the andy speech is the marker please, let’s try it, and the marker wants it. Based on research results found the most dominant strategy used in bringing the show is a marker of politeness.Key words: the strategy of language politeness, the sign of language politeness, Andy F Noya.